Thermal Conductivity of Frozen and Unfrozen Gas-Saturated Soils - Evgeny Chuvilin; Dinara Davletshina; Boris Bukhanov; Sergey Grebenkin (Geosciences, 2023)
Arctic permafrost often contains gas-saturated horizons. The gas component in freezing and frozen soils can exist under different pressures, which are expected to affect their properties and behavior. The effect of pore gas pressure on the thermal conductivity of frozen and unfrozen silt loam saturated with methane or carbon dioxide at pressures below the hydrate formation conditions is observed in the current study. The variable gas pressure and temperature conditions are simulated in a specially designed pressure cell, which allows thermal conductivity measuring in pressurized samples at positive and negative temperatures. The experiments using natural samples collected near the gas emission crater (Yamal Peninsula) show that thermal conductivity is sensitive to pore gas pressure even at high moisture contents. The thermal conductivity of methane-saturated soil becomes 4% and 6% higher in frozen and unfrozen samples, respectively, as the gas pressure increases from 0.1 MPa to 2 MPa. In the case of CO2 saturation, the respective thermal conductivity increase in frozen and unfrozen samples reaches 25% and 15% upon pressure change from 0.1 to 0.9 MPa. The results stimulate further special studies of the effects of gas type and pressure on the thermal properties of closed gas-saturated taliks, of which the pore pressure is increasing during freezing up.